Implementation Of Mobile Application For A Museum By Using Internet Of Things Technology - Anthony Widjaja; James Purnama; Maulahikmah Galinium (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2019)
This project is conducted based on the Nawacita policy from President Joko Widodo. Tourists tend to explore the attraction independently instead of using a tour guide, but there are minimum supporting facilities because of the limitations of detailed information on tourist attraction in various languages that are not interesting and less interactive. The objectives of the research are to develop an Internet of Things based mobile application named eTourGuide that uses a location-based service to get information about the content interestingly and interactively inside a museum. The location-based service uses beacon that broadcast Bluetooth Low Energy (BLE) signal. Development of the research includes several experiments for gathering the data optimally. After completing the development, user experience questionnaire is required to evaluate the result of user’s experience after using the application. The result shows positive results of user’s experience after using the application.